A Popular Dictionary of Hinduism - Werner, Karel (Taylor & Francis, 1997)
A multi-purpose reference work which should become an indispensable companion for anybody who comes into touch with Hinduism. Includes a dictionary of Sanskrit and vernacular terms; a glossary of terms and concepts; and a survey of the historical development of Hinduism.